Bone scintigraphy in clinical routine - Müller, Vika (Radiology and oncology (Ljubljana), 2001)
Background. In 1971, bone scintigraphy was performed the first time using 99mTc-labeled polyphosphonates. Since that time, bone scintigraphy has become one of the most frequent diagnostic procedures in nuclear medicine departments. However, in the last decade, indications for this skeletal imaging procedure have been changing continuously. This paper, therefore givesa concise review of the current spectrum of indications for bone scintigraphy and its realization. Conclusions. Just as many other nuclear medicine procedures, the bone scintigraphy has a high sensitivity, and the changes of the bone metabolism are seen often earlier than the changes in bonestructure developing after x-ray. Therefore, occult lesions in the whole skeleton might be detected early by bone scintigraphy. On the other hand, boneturnover is increased in various bone diseases. Consequently, bone scintigraphy usually has a low specificity, and differential diagnosis of the underlying etiology is often not feasible. However, there-phase bone scintigraphy and SPECT can significantly increase the specificity in some skeletal areas.
Keywords: bolezni kosti; Bone diseases; Bone neoplasms; okostje; Radionuclide imaging; scintigrafija; slikovna diagnostika; Technetium compounds